Method for manufacturing alkali-free glass substrate

The continuous production of alkaline glass using a SiO2-Al2O3-RO system with controlled β-OH value and electrical melting, combined with drainage heating and magnetic sorting, addresses the issue of metal bumps in glass substrates, enhancing their quality for oxide TFT applications.

JP7623629B2Active Publication Date: 2025-01-29NIPPON ELECTRIC GLASS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020209435
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-17
Publication Date
2025-01-29
Estimated Expiration
2040-12-17

Smart Images

  • Figure 0007623629000002
    Figure 0007623629000002
  • Figure 0007623629000003
    Figure 0007623629000003
  • Figure 0007623629000001
    Figure 0007623629000001
Patent Text Reader

Abstract

To provide a method for producing an alkali-free glass substrate, the method being capable of producing an alkali-free glass substrate having a small number of bumps.SOLUTION: The present invention discloses a method for continuously producing an alkali-free glass substrate of SiO2-Al2O3-RO (RO represents one or more selected from MgO, CaO, BaO, SrO and ZnO), the method comprising: a step for preparing a starting material batch that contains a tin compound but does not substantially contain an arsenic compound or an antimony compound; a step for electrically melting the prepared starting material batch in a melting furnace which can be heated by electrical conduction by electrodes; and a step for shaping the molten glass into a plate by the down-draw method. The β-OH value of the obtained glass is 0.05 / mm or more, while the number of metal bumps therein is 20 / ton or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an alkali-free glass substrate, and more particularly to a method for producing an alkali-free glass substrate suitable for displays and the like equipped with thin film transistors (TFTs) having an oxide film such as indium gallium zinc oxide (IGZO). [Background technology]

[0002] In general, a glass substrate is used as a supporting substrate for flat panel displays. Electric circuit patterns such as TFTs are formed on the surface of the glass substrate. For this reason, non-alkali glass substrates that do not substantially contain alkali metal components are used for this type of glass substrate so as not to adversely affect the TFTs.

[0003] Known methods for forming alkali-free glass substrates include down-draw methods, typified by the overflow down-draw method.

[0004] The down-draw method is a method of stretching molten glass downward to form a plate shape. The overflow down-draw method, which is one type of down-draw method, is a method of forming a glass ribbon by stretching molten glass overflowing from both sides of a forming body having a substantially wedge-shaped cross section downward. The molten glass overflowing from both sides of the forming body flows down along both sides of the forming body and joins below the forming body. Therefore, in the overflow down-draw method, the surface of the glass ribbon does not come into contact with anything other than air and is formed by surface tension, so that a glass substrate with a flat surface can be obtained without foreign matter adhering to the surface even if the surface is not polished after forming. In addition, the overflow down-draw method has the advantage of being easy to form a thin glass substrate.

[0005] Furthermore, examples of a method for melting an alkali-free glass substrate include electric melting, which is described in Patent Document 1. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2014-88306 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, the glass described in Patent Document 1 has a problem in that it is prone to the generation of bumps.

[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a method for producing an alkali-free glass substrate having a reduced number of bumps. [Means for solving the problem]

[0009] The method for producing alkali-free glass of the present invention is a method for continuously producing an alkali-free glass substrate of SiO2-Al2O3-RO (RO is one or more of MgO, CaO, BaO, SrO, and ZnO) system, which includes the steps of preparing a raw material batch containing a tin compound and substantially free of arsenic compounds and antimony compounds, electrically melting the prepared raw material batch in a melting furnace capable of heating by applying current through electrodes, and forming the molten glass into a plate by a down-draw method, and is characterized in that the β-OH value of the obtained glass is 0.05 / mm or more and the number of metal particles is 20 / ton or less. Here, the "metal particles" are counted as metal particles when metal particles of 1 μm or more are observed in the observation field by a stereomicroscope, and the number of metal particles per ton is calculated from the size of the glass used for the measurement.

[0010] As a result of various investigations, the inventors have found that when glass is electrically melted, SnO2 in the glass is reduced by Fe, Cr, Ni, etc. contained in the raw material batch, and metal particles containing Sn are precipitated in the glass, as shown in formula 1 (x and y are coefficients, and M represents Fe, Cr, and / or Ni). Furthermore, they have also found that by increasing the β-OH value of glass, Fe, Cr, Ni, etc. bond with OH groups in the glass, as shown in formula 2 (z is a coefficient, and M represents Fe, Cr, and / or Ni), making it difficult to reduce SnO2 and difficult to precipitate metal particles in the glass.

[0011] (Formula 1) SnO2+(2x / y)M⇒ Sn+(2 / y)MxOy (Formula 2) (z)Si-OH+(z)M⇒ (z)Si-OM+(z / 2)H2

[0012] "Alkali-free glass" means glass to which no alkali metal oxide components are intentionally added, specifically glass in which the content of alkali metal oxides (Li2O, Na2O, and K2O) in the glass composition is 2000 ppm (by mass) or less. "Produced continuously" means that glass is produced continuously for a certain period of time in a continuous melting furnace such as a tank furnace. "SiO2-Al2O3-RO system" means a glass composition system containing SiO2, Al2O3, and RO as essential components. "Electric melting" means a melting method in which electricity is passed through glass and the glass is melted by the Joule heat generated by the electric current. Note that this does not exclude melting methods that supplementarily use radiant heating by a heater or burner. "Substantially free of arsenic and antimony" means that glass raw materials or glass cullets containing these components are not intentionally added to the glass batch. More specifically, it means that the resulting glass contains 50 ppm or less of arsenic as As2O3 and 50 ppm or less of antimony as Sb2O3 on a molar basis. The "down-draw method" is a general term for a forming method in which molten glass is formed while being continuously drawn downward.

[0013] The present invention is also characterized in that the glass is melted by electrical heating. When electrical heating is used, the amount of energy per mass required to obtain molten glass is reduced, thereby reducing the environmental load.

[0014] In the present invention, it is preferable to adjust the β-OH value and the number of metal particles of the resulting glass by adjusting the glass raw materials and / or the melting conditions.

[0015] In the present invention, the effect is more remarkable when radiant heating by burner combustion is not used in combination. "Radiant heating by burner combustion is not used in combination" means that radiant heating by burner combustion is not used at all during normal production, and does not exclude the use of a burner during start-up of production (when heating up). It also does not exclude the use of radiant heating by a heater in combination during start-up of production or normal production. Note that the start-up of production refers to the period from when the raw material batch melts to become molten glass and becomes electrically heated.

[0016] In the present invention, when producing an alkali-free glass substrate further containing B2O3 as a glass composition, it is preferable to use orthoboric acid in at least a part of the glass raw material serving as a boron source.

[0017] The above-mentioned composition makes it easier to adjust the water content of the resulting glass. In addition, since the boron component (B2O3) is a component that improves the meltability of glass, the above-mentioned composition makes it easier to obtain glass with excellent productivity.

[0018] In the present invention, it is preferable that the raw material batch contains a hydroxide raw material.

[0019] In the present invention, when a non-alkali glass substrate is manufactured by adding glass cullet to a raw material batch, it is preferable to use glass cullet having a β-OH value of 0.05 / mm or more as at least a part of the glass cullet. Here, "glass cullet" means defective glass generated during glass manufacturing, recycled glass collected from the market, etc. The "β-OH value" refers to a value obtained by measuring the transmittance of glass using FT-IR and using the following formula.

[0020] β-OH value = (1 / X)log(T1 / T2) X: Glass thickness (mm) T1: Reference wavelength 3846cm -1 Transmittance (%) T2: Hydroxyl group absorption wavelength 3600cm -1 Minimum transmittance (%) near

[0021] In the present invention, it is preferable to carry out the step of removing metals by passing the glass cullet through a magnetic separator two or more times.

[0022] Recycled glass cullet contains metals including Fe, Cr, Ni, etc., which are used in blending equipment, etc. By passing the glass cullet through a magnetic separator two or more times, metals including Fe, Cr, Ni, etc. can be sufficiently removed, making it difficult for metals including Fe, Cr, Ni, etc. to be mixed into the raw material batch. As a result, metal particles including Sn are less likely to precipitate in the glass.

[0023] In the present invention, the strain point of the obtained glass is preferably at least 690° C. Here, the “strain point” is a value measured based on the method of ASTM C336-71.

[0024] In the present invention, the thermal shrinkage of the obtained glass is preferably 25 ppm or less. Here, the "thermal shrinkage" is a value measured under the conditions that the glass is heated from room temperature to 500°C at a rate of 5°C / min, held at 500°C for 1 hour, and then cooled at a rate of 5°C / min.

[0025] The thermal shrinkage is measured by the following method. First, as shown in FIG. 1(a), a rectangular sample G of 160 mm×30 mm is prepared as a sample of the glass plate 1. Markings M are formed on both ends of the long side of the rectangular sample G at positions 20 to 40 mm away from the edge using #1000 waterproof abrasive paper. Then, as shown in FIG. 1(b), the rectangular sample G on which markings M are formed is folded in two along the direction perpendicular to the markings M to prepare sample pieces Ga and Gb. Then, only one of the sample pieces Gb is subjected to a heat treatment in which the temperature is raised from room temperature (25° C.) to 500° C. at a rate of 5° C. / min, and the sample is kept at 500° C. for 1 hour, and then the temperature is lowered to room temperature at a rate of 5° C. / min. After the above heat treatment, as shown in Fig. 1(c), the sample piece Ga that was not heat treated and the sample piece Gb that was heat treated were arranged in parallel, and the positional deviations (ΔL1, ΔL2) of the markings M of the two sample pieces Ga and Gb were read using a laser microscope, and the thermal shrinkage rate was calculated using the following formula, where l0 is the initial distance between the markings M.

[0026] Heat shrinkage rate = [{ΔL1(μm)+ΔL2(μm)}×10 3 ] / l0(mm) (ppm)

[0027] By adopting the above-mentioned structure, it is possible to obtain a glass substrate suitable for forming an oxide TFT.

[0028] In the present invention, it is preferable to use the present invention in the manufacture of a glass substrate on which an oxide TFT is formed. [Brief description of the drawings]

[0029] [Figure 1] FIG. 4 is a plan view for explaining a procedure for measuring the thermal shrinkage rate of a glass substrate. [Diagram 2] 1 is a graph showing the relationship between β-OH value and metal particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] The method for producing an alkali-free glass of the present invention will now be described in detail.

[0031] The method of the present invention includes the steps of preparing a raw material batch, electrically melting the prepared batch, and forming the molten glass into a sheet shape.

[0032] (1) The process of preparing raw material batches First, glass raw materials are prepared so as to have a composition of SiO2-Al2O3-RO (RO is one or more of MgO, CaO, BaO, SrO and ZnO). A suitable glass composition will be described later.

[0033] Silica sand, stone powder (SiO2), etc. can be used as the silicon source.

[0034] As the aluminum source, alumina (Al2O3), aluminum hydroxide (Al(OH)3), etc. can be used.

[0035] Orthoboric acid (H3BO3) or boric anhydride (B2O3) can be used as a boron source. Since orthoboric acid contains water of crystallization, if the ratio of orthoboric acid used is large, the water content of the glass can be adjusted to be relatively high. For this reason, it is preferable to use both orthoboric acid and boric anhydride and adjust their ratio according to the desired β-OH content.

[0036] Examples of alkaline earth metal sources that can be used include calcium carbonate (CaCO3), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), barium carbonate (BaCO3), barium nitrate (Ba(NO3)2), strontium carbonate (SrCO3), and strontium nitrate (Sr(NO3)2).

[0037] Zinc oxide (ZnO) or the like can be used as the zinc source.

[0038] Zircon (ZrSiO4) and the like can be used as the zirconia source. When using Zr-containing refractories such as zirconia electrocast refractories and dense zircon as the refractories constituting the melting furnace, zirconia components may be eluted from the refractories. These eluted components may also be used as the zirconia source.

[0039] Titanium oxide (TiO2) or the like can be used as the titanium source.

[0040] As the phosphorus source, aluminum metaphosphate (Al(PO3)3), magnesium pyrophosphate (Mg2P2O7), etc. can be used.

[0041] Tin oxide (SnO2) and the like can be used as the tin compound. When using tin oxide, the average particle size D 50 It is preferable to use tin oxide having an average particle size D of 0.3 to 50 μm, 2 to 50 μm, and particularly 5 to 50 μm. 50 If the average particle size D of the tin oxide powder is small, the particles will aggregate and become clogged in the mixing plant. 50 If the melting reaction of the tin oxide powder into the molten glass is delayed, and the clarification of the molten glass does not progress. As a result, oxygen gas cannot be released sufficiently at the appropriate time during the glass melting process, and bubbles tend to remain in the glass product, making it difficult to obtain a product with excellent bubble quality. It also tends to cause the appearance of undissolved SnO2 crystals in the glass product.

[0042] In the present invention, the raw material batch may contain a carbonate raw material. The carbonate raw material can make the fining agent SnO2 function efficiently. For example, calcium carbonate (CaCO3), barium carbonate (BaCO3), strontium carbonate (SrCO3), etc. can be used as the carbonate raw material.

[0043] In the present invention, the raw material batch may contain a nitrate raw material. The nitrate raw material can make the fining agent SnO2 function efficiently. As the nitrate raw material, for example, barium nitrate (Ba(NO3)2), strontium nitrate (Sr(NO3)2), etc. can be used.

[0044] In the present invention, the raw material batch may contain a hydroxide raw material. The hydroxide raw material can increase the water content in the glass. As the hydroxide raw material, aluminum hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2), calcium hydroxide (Ca(OH)2), etc. can be used.

[0045] In the present invention, it is preferable that the batch is substantially free of arsenic compounds and antimony compounds. If these compounds are present, they corrode the electrodes, making it difficult to perform stable electric melting over a long period of time. Furthermore, these compounds are undesirable from an environmental standpoint.

[0046] In the present invention, it is preferable to use glass cullet in addition to the above-mentioned glass raw material. When using glass cullet, the use ratio of glass cullet to the total amount of the raw material batch is preferably 1 mass% or more, 5 mass% or more, particularly 10 mass% or more. There is no restriction on the upper limit of the use ratio of glass cullet, but it is preferably 50 mass% or less, 40 mass% or less, particularly 30 mass% or less. It is also preferable that at least a part of the glass cullet used is glass cullet made of glass having a β-OH value of 0.05 / mm or more, 0.07 / mm or more, particularly 0.1 / mm or more. If the β-OH value of the glass cullet is too high, there is a risk that the strain point of the glass will be too low, so the upper limit of the β-OH value of the glass cullet is preferably 0.4 / mm or less.

[0047] It is also preferable to carry out the process of removing metals by passing the glass cullet through a magnetic separator at least two times, preferably at least three times, and particularly preferably at least five times. In this way, metals including Fe, Cr, Ni, etc. that reduce SnO2 in the glass are less likely to be mixed into the raw material batch. As a result, metal particles including Sn are less likely to precipitate. Note that, although the amount of metals including Fe, Cr, Ni, etc. that are mixed in can be reduced by increasing the number of times of the above process, it is preferable that the number of times of the above process is 10 or less from the viewpoint of cost.

[0048] (2) Electric melting of the prepared raw material batch Next, the prepared raw material batch is charged into a melting furnace and electrically melted.

[0049] The melting furnace has a plurality of electrodes, and when electricity is applied between the electrodes, electricity flows through the molten glass, and the glass is continuously melted by the Joule heat. Note that radiation heating by a heater or burner may be used as an auxiliary means.

[0050] Molybdenum electrodes are preferably used as the electrodes because they have a high degree of freedom in terms of the location and shape of the electrodes, and because even non-alkali glass, which does not easily conduct electricity, can be optimally located and shaped, making it easy to apply electrical heating. The electrode shape is preferably rod-shaped. If the electrode is rod-shaped, it is possible to arrange a desired number of electrodes at any position on the side wall or bottom wall of the melting furnace while maintaining a desired distance between the electrodes. The electrodes are preferably arranged in pairs on the wall (side wall, bottom wall, etc.) of the melting furnace, especially on the bottom wall, with a short distance between the electrodes. If the glass contains arsenic or antimony, the molybdenum electrodes cannot be used because they corrode, and instead, it is necessary to use tin electrodes, which are not corroded by these components. However, since the freedom in terms of the location and shape of the tin electrodes is very low, it is difficult to electrically melt non-alkali glass.

[0051] The raw material batch fed into the melting furnace is melted by electrical heating to become molten glass (molten glass). At this time, the tin compounds contained in the raw material batch dissolve in the molten glass and act as a fining agent. More specifically, the tin component releases oxygen bubbles during the temperature rise process. The released oxygen bubbles expand the bubbles contained in the molten glass, causing them to rise to the surface and be removed from the glass. Furthermore, the tin component absorbs the oxygen bubbles during the temperature fall process, eliminating any bubbles remaining in the glass.

[0052] The glass molten in the melting furnace is supplied to the forming apparatus, but it may be supplied to the forming apparatus after passing through a fining tank, stirring tank, condition adjustment tank, etc., which are arranged between the melting furnace and the forming apparatus. In addition, it is preferable that at least the surface of the communication flow path connecting the melting furnace and the forming apparatus (or each tank provided therebetween) that comes into contact with the glass is made of platinum or a platinum alloy in order to prevent contamination of the glass.

[0053] (3) The process of forming the molten glass into sheets Next, the glass molten in the melting furnace is fed to a forming device and formed into a sheet by the down-draw method.

[0054] As the down-draw method, it is preferable to adopt the overflow down-draw method. The overflow down-draw method is a method in which molten glass is made to overflow from both sides of a trough-shaped refractory having a wedge-shaped cross section, and the overflowed molten glass is made to join at the lower end of the trough-shaped refractory while being stretched downward to form the glass into a plate shape. In the overflow down-draw method, the surface to be the surface of the glass substrate is not in contact with the trough-shaped refractory, and is formed in a free surface state. For this reason, a glass substrate that is not polished and has good surface quality can be produced inexpensively, and the glass can be easily made large and thin. The structure and material of the trough-shaped refractory used in the overflow down-draw method are not particularly limited as long as they can achieve the desired dimensions and surface accuracy. In addition, the method of applying force when performing the downward stretching is not particularly limited. For example, a method in which a heat-resistant roll having a sufficiently large width is rotated in contact with the glass to stretch it may be adopted, or a method in which a plurality of pairs of heat-resistant rolls are brought into contact with only the vicinity of the end face of the glass to stretch it may be adopted. In addition to the overflow downdraw method, for example, a slot down method or the like can also be adopted.

[0055] The glass formed into a plate shape in this manner is cut to a predetermined size and, if necessary, is subjected to various chemical or mechanical processes to form a glass substrate.

[0056] (4) Composition of alkali-free glass The composition of the alkali-free glass to which the manufacturing method of the present invention can be suitably applied is, in mass%, SiO2 50-70%, Al2O3 15-25%, B2O3 2-7.5%, MgO 0-10%, CaO 0-10%, SrO 0-10%, BaO 0-15%, ZnO 0-5%, ZrO2 0-1%, TiO2 0-5%, P2O 50-10%, SnO2 0.1-0.5%, and glass that does not substantially contain As2O3 and Sb2O3. The reasons for limiting the content of each component as described above are as follows. In the explanation of the content of each component, % indicates mass % unless otherwise specified.

[0057] SiO2 is a component that forms the skeleton of glass. The lower limit of the SiO2 content is preferably 50%, 51%, 51.5%, 52%, 55%, 56%, 57%, and particularly preferably 58%. The upper limit of the SiO2 content is preferably 70%, 69%, 68%, 67%, 66%, 65%, 64%, 63%, and particularly preferably 62%. If the SiO2 content is too low, the density becomes too high and the acid resistance is easily reduced. On the other hand, if the SiO2 content is too high, the high-temperature viscosity becomes high and the melting property is easily reduced. In addition, devitrified crystals such as cristobalite are easily precipitated, and the liquidus temperature is easily increased.

[0058] Al2O3 is a component that forms the skeleton of glass, increases the strain point and Young's modulus, and suppresses phase separation. The lower limit of the content of Al2O3 is preferably 15%, 15.5%, 16%, 16.5%, 17%, or 17.5%, and particularly preferably 18%. The upper limit of the content of Al2O3 is preferably 25%, 24%, 23%, 22%, or 21.5%, and particularly preferably 21%. If the content of Al2O3 is too low, the strain point and Young's modulus tend to decrease, and the glass tends to undergo phase separation. On the other hand, if the content of Al2O3 is too high, devitrified crystals such as mullite and anorthite tend to precipitate, and the liquidus temperature tends to increase.

[0059] B2O3 is a component that enhances meltability and devitrification resistance. The lower limit of the B2O3 content is preferably 2%, 2.2%, and particularly 2.5%. The upper limit of the B2O3 content is preferably 7.5%, and particularly 7%. If the B2O3 content is too low, the meltability and devitrification resistance are likely to decrease, and the resistance to hydrofluoric acid-based chemicals such as buffered hydrofluoric acid is likely to decrease. There is also a risk that the amount of moisture carried over from the batch will be too small. On the other hand, if the B2O3 content is too high, the strain point and Young's modulus are likely to decrease.

[0060] MgO is a component that reduces high-temperature viscosity and increases melting property, and among alkaline earth metal oxides, it is a component that significantly increases Young's modulus. The lower limit of the MgO content is preferably 0%, 0.1%, 0.5%, 1%, 1.5%, and particularly preferably 2%. The upper limit of the MgO content is preferably 10%, 9%, 8%, 7.5%, 7%, 6%, and particularly preferably 5%. If the MgO content is too low, the melting property and Young's modulus are likely to decrease. On the other hand, if the MgO content is too high, the devitrification resistance is likely to decrease and the strain point is likely to decrease.

[0061] CaO is a component that reduces high-temperature viscosity and significantly improves melting property without lowering the strain point. In addition, since the raw material introduced is relatively inexpensive among alkaline earth metal oxides, it is a component that reduces raw material costs. The lower limit of the CaO content is preferably 0%, 0.1%, 1%, 2%, 3%, and particularly 3.5%. The upper limit of the CaO content is preferably 10%, 9%, 8%, and particularly 7%. If the CaO content is too low, it is difficult to enjoy the above effects. On the other hand, if the CaO content is too high, the glass is easily devitrified and the thermal expansion coefficient is easily increased.

[0062] SrO is a component that suppresses phase separation and enhances devitrification resistance. Furthermore, it is a component that reduces high-temperature viscosity and enhances melting property without lowering the strain point. It is also a component that suppresses an increase in liquidus temperature. The lower limit of the SrO content is preferably 0%, 0.1%, and particularly 0.3%. The upper limit of the SrO content is preferably 10%, 9%, 8%, 7%, 6%, and particularly 5%. If the SrO content is too low, it becomes difficult to enjoy the above effects. On the other hand, if the SrO content is too high, the density becomes too high and devitrification crystals containing SrO are easily precipitated, and the devitrification resistance is easily reduced.

[0063] BaO is a component that significantly improves devitrification resistance. The lower limit of the BaO content is preferably 0%, 0.1%, or 0.5%, particularly 1%. The upper limit of the BaO content is preferably 15%, 14%, 13%, 12%, or 11%, particularly 10.5%. If the BaO content is too low, it becomes difficult to enjoy the above effects. On the other hand, if the BaO content is too high, the density becomes too high and the melting property tends to decrease. In addition, devitrification crystals containing BaO tend to precipitate, and the liquidus temperature tends to increase.

[0064] ZnO is a component that enhances meltability. The ZnO content is preferably 0 to 5%, 0 to 4%, 0 to 3%, and particularly preferably 0 to 2%. If the ZnO content is too high, the glass is prone to devitrification and the strain point is prone to decrease.

[0065] ZrO2 is a component that enhances chemical durability. The lower limit of the ZrO2 content is preferably 0%, and more preferably 0.01%. The upper limit of the ZrO2 content is preferably 1%, 0.5%, 0.2%, 0.1%, and more preferably 0.05%. If the ZrO2 content is too high, ZrSiO4 devitrification particles are more likely to occur.

[0066] TiO2 is a component that reduces high-temperature viscosity and enhances melting property. It is also a component that suppresses solarization. The content of TiO2 is preferably 0 to 5%, 0 to 4%, 0 to 3%, 0 to 2%, 0 to 1%, and particularly preferably 0 to 0.1%. If the content of TiO2 is too high, the glass becomes colored and the transmittance is easily reduced.

[0067] P2O5 is a component that increases the strain point and can suppress the precipitation of devitrified crystals of alkaline earth aluminosilicates such as anorthite. The content of P2O5 is preferably 0 to 10%, 0 to 9%, 0 to 8%, 0 to 7%, 0 to 6%, 0 to 5%, 0 to 4%, and particularly preferably 0 to 3%. If the content of P2O5 is too high, the glass is prone to phase separation.

[0068] SnO2 is a component that has a good clarification effect in the high temperature range, increases the strain point, and reduces the high-temperature viscosity. It also has the advantage of not corroding the molybdenum electrode. The lower limit of the SnO2 content is preferably 0.1%, particularly 0.15%. The upper limit of the SnO2 content is preferably 0.5%, 0.45%, 0.4%, 0.35%, particularly 0.3%. If the SnO2 content is too low, it becomes difficult to enjoy the above effects. On the other hand, if the SnO2 content is too high, devitrified crystals of SnO2 are easily precipitated, and the precipitation of devitrified crystals of ZrO2 is easily promoted.

[0069] It is preferable that As2O3 and Sb2O3 are not substantially contained from the viewpoint of the environment and from the viewpoint of preventing erosion of electrodes. Here, "substantially not contained" means that glass raw materials or glass cullets containing these components are not intentionally added to the glass batch. More specifically, it means that arsenic is 50 ppm or less as As2O3 and antimony is 50 ppm or less as Sb2O3 in the obtained glass. These components are useful as fining agents, but should not be used because they corrode molybdenum electrodes and make electric melting on an industrial scale difficult. It is also preferable that they are not used from the viewpoint of the environment.

[0070] In addition to the above ingredients, other ingredients may be contained in a total amount of up to 5%.

[0071] The glass may contain Cl and F, but the Cl content is preferably less than 0.1%, particularly less than 0.05%, and the F content is preferably less than 0.1%, particularly less than 0.05%. Also, Cl+F (the total amount of Cl and F) is preferably less than 0.1%.

[0072] (5) Characteristics of alkali-free glass substrates Next, the alkali-free glass substrate obtained by the method of the present invention will be described.

[0073] The alkali-free glass substrate obtained by the method of the present invention is made of glass having a β-OH value of 0.05 / mm or more, 0.07 / mm or more, 0.1 / mm or more, 0.12 / mm or more, 0.15 / mm or more, 0.18 / mm or more, particularly 0.2 / mm or more. In this way, it is possible to sufficiently reduce the number of metal particles. If the β-OH value is too large, the strain point of the glass does not become sufficiently high, making it difficult to reduce the thermal shrinkage rate, so the upper limit of the β-OH value is preferably 0.4 / mm or less, particularly 0.35 / mm or less.

[0074] The alkali-free glass substrate obtained by the method of the present invention is made of glass having a number of metal particles of 20 particles / ton or less, 10 particles / ton or less, 5 particles / ton or less, and particularly 3 particles / ton or less. The lower limit of the number of metal particles is not particularly limited, but is practically 0.1 particles / ton or more.

[0075] The alkali-free glass plate obtained by the method of the present invention preferably has a thermal shrinkage of 25 ppm or less, 20 ppm or less, 19 ppm or less, 18 ppm or less, 17 ppm or less, 16 ppm or less, 15 ppm or less, 14 ppm or less, and particularly 13 ppm or less when the glass is heated from room temperature to 500°C at a rate of 5°C / min, held at 500°C for 1 hour, and then cooled at a rate of 5°C / min. If the thermal shrinkage is large, it becomes difficult to use the glass as a substrate for forming an oxide TFT. Although there is no lower limit for the thermal shrinkage, it is preferably 2 ppm or more, and particularly preferably 3 ppm or more.

[0076] The alkali-free glass plate obtained by the method of the present invention is preferably made of glass having a strain point of 690° C. or more, 700° C. or more, 705° C. or more, particularly 710° C. or more. In this way, it becomes easier to suppress the thermal shrinkage of the glass plate in the manufacturing process of the oxide TFT. If the strain point is too high, the temperature during molding or melting becomes too high, which tends to increase the manufacturing cost of the glass plate, so the upper limit of the strain point is preferably 750° C. or less, 740° C. or less, particularly 730° C. or less.

[0077] The alkali-free glass plate obtained by the method of the present invention has a viscosity of 10 2.5 It is preferable that the glass has a temperature in dPa·s of 1630° C. or less, 1620° C. or less, 1610° C. or less, 1600° C. or less, 1590° C. or less, particularly 1580° C. or less. 2.5 If the temperature at dPa·s is too high, the glass will be difficult to melt, the manufacturing cost of the glass sheet will rise, and defects such as bubbles will easily occur. 2.5 If the temperature in dPa·s is too low, it becomes difficult to design a high viscosity at the liquidus temperature. 2.5 The lower limit of the temperature at dPa·s is preferably 1500°C or higher, 1510°C or higher, and particularly preferably 1520°C or higher. 2.5 The "temperature equivalent to dPa·s" is a value measured using the platinum ball pulling method.

[0078] The alkali-free glass plate obtained by the method of the present invention is preferably made of glass having a liquidus temperature of less than 1250°C, less than 1240°C, less than 1230°C, less than 1220°C, less than 1210°C, particularly less than 1200°C. In this way, devitrification crystals are less likely to occur during glass production, and it is easy to prevent a situation in which productivity is reduced. Furthermore, since it is easy to form the glass by the overflow downdraw method, it is easy to improve the surface quality of the glass plate and reduce the manufacturing cost of the glass plate. And, from the viewpoint of the recent increase in the size of glass plates and the high definition of displays, it is very important to improve the devitrification resistance in order to suppress devitrification products that can become surface defects as much as possible. The liquidus temperature is an index of devitrification resistance, and the lower the liquidus temperature, the better the devitrification resistance. The "liquidus temperature" refers to the temperature at which devitrification (crystalline foreign matter) is observed in the glass when glass powder that passes through a standard 30 mesh (500 μm) sieve and remains on a 50 mesh (300 μm) sieve is placed in a platinum boat and held in a temperature gradient furnace set at 1100°C to 1350°C for 24 hours, and then the platinum boat is removed.

[0079] The alkali-free glass sheet obtained by the method of the present invention has a liquidus viscosity of 10 4.0 dPa s or more, 10 4.2 dPa s or more, 10 4.4dPa s or more, 10 4.5 dPa s or more, 10 4.6 dPa s or more, 10 4.7 dPa s or more, 10 4.8 dPa s or more, 10 4.9 dPa s or more, especially 10 5.0 It is preferable that the glass is made of glass having a viscosity of 1000 dPa·s or more. In this way, devitrification is less likely to occur during forming, making it easier to form glass sheets using the overflow downdraw method, which results in improved surface quality of the glass sheets and reduced manufacturing costs for glass sheets. The liquidus viscosity is an index of formability, and the higher the liquidus viscosity, the better the formability. The "liquidus viscosity" refers to the viscosity of glass at the liquidus temperature, and can be measured, for example, by the platinum ball pull-up method.

[0080] The alkali-free glass plate obtained by the method of the present invention has a substrate area of ​​4 m 2 If the substrate area is too small, it becomes difficult to efficiently manufacture large LCD and OLED displays equipped with TFTs having oxide films such as IGZO. EXAMPLES

[0081] Next, the glass produced by the method of the present invention will be described. Table 1 shows examples (Nos. 1 to 6) of the present invention.

[0082] [Table 1]

[0083] First, silica sand, aluminum oxide, orthoboric acid, boric anhydride, calcium carbonate, strontium carbonate, strontium nitrate, barium carbonate, and stannic oxide were mixed and prepared to obtain the composition shown in Table 1. Glass cullet with the same composition as the target composition (β-OH value 0.2 / mm, used at 35 mass% of the total amount of the raw material batch) was also used. The glass cullet was passed through a magnetic separator twice to remove metals.

[0084] Next, the glass raw materials were fed into an electric melting furnace not using burner combustion and melted, and then in a fining tank and an adjusting tank, the molten glass was clarified and homogenized, and its viscosity was adjusted to a value suitable for molding.

[0085] The molten glass was then fed to an overflow downdraw forming apparatus, formed into a plate, and cut to obtain a glass sample having a thickness of 0.5 mm. The molten glass leaving the melting furnace was fed to the forming apparatus while being in contact with only platinum or a platinum alloy.

[0086] The obtained glass samples were observed under a stereo microscope at 50x magnification, and if metal particles of 1 μm or more were observed within the observation field, they were counted as metal particles, and the number of metal particles per ton was calculated from the size of the glass used for measurement. The results are shown in Table 1.

[0087] As is clear from Table 1, samples No. 1 to 6 had a large β-OH value of 0.12 / mm or more, and therefore the number of metal particles was small at 13.8 pieces / ton or less. Figure 2 shows a plot of the β-OH value on the horizontal axis and the number of metal particles on the vertical axis. As is clear from Figure 2, the larger the β-OH value, the fewer the number of metal particles.

[0088] The β-OH value of the glass was determined by measuring the transmittance of the glass using FT-IR and using the following formula:

[0089] β-OH value = (1 / X)log10(T1 / T2) X: Glass thickness (mm) T1: Reference wavelength 3846cm -1 Transmittance (%) T2: Hydroxyl group absorption wavelength 3600cm -1 Minimum transmittance (%) near

Claims

1. SiO 2 -Al 2 O 3 A method for continuously producing an alkali-free glass substrate of an -RO (RO is one or more of MgO, CaO, BaO, SrO and ZnO), comprising the steps of: preparing a feed batch containing tin compounds and substantially free of arsenic and antimony compounds; A step of electrically melting the prepared raw material batch in a melting furnace capable of electrically heating using electrodes; and forming the molten glass into a sheet shape by a down-draw method. A method for producing an alkali-free glass substrate, characterized in that the β-OH value of the obtained glass is 0.18 / mm or more and the number of metal particles containing reduced Sn is 5 / ton or less.

2. 2. The method for producing an alkali-free glass substrate according to claim 1, wherein the β-OH value and the number of metal particles of the resulting glass are adjusted by adjusting the glass raw materials and / or the melting conditions.

3. 3. The method for producing an alkali-free glass substrate according to claim 1, wherein radiant heating by burner combustion is not used in combination.

4. The glass composition further includes B 2 O 3 The method for producing an alkali-free glass substrate according to any one of claims 1 to 3, characterized in that orthoboric acid is used in at least a part of a glass raw material serving as a boron source.

5. 5. The method for producing an alkali-free glass substrate according to claim 1, wherein the raw material batch contains a hydroxide raw material.

6. 6. The method for producing an alkali-free glass substrate according to any one of claims 1 to 5, characterized in that the method comprises adding glass cullet to a raw material batch to produce an alkali-free glass substrate, and at least a part of the glass cullet is made of glass having a β-OH value of 0.05 / mm or more.

7. 7. The method for producing an alkali-free glass substrate according to claim 6, wherein the step of removing metals by passing the glass cullet through a magnetic separator is carried out two or more times.

8. 8. The method for producing an alkali-free glass substrate according to claim 1, wherein the strain point of the obtained glass is 690° C. or higher.

9. 9. The method for producing an alkali-free glass substrate according to claim 1, wherein the thermal shrinkage of the obtained glass is 25 ppm or less.

10. 10. The method for producing an alkali-free glass substrate according to claim 1, which is used for producing a glass substrate on which an oxide TFT is formed.

Citation Information

Patent Citations

  • Method for producing glass substrate, and production device therefor

    JP2014088306A

  • Production method of glass substrate

    JP2020132444A

  • Alkali-free glass substrate production method

    WO2018123505A1

  • Method for producing alkali-free glass substrate, and alkali-free glass substrate

    WO2019049768A1